The Role of Social Support in Increasing Socialization Ability ADHD (Attention-Deficit and Hyperactivity Disorder) Children at Suryo Bimo Kresno Elementary School - Sania Qotrun Nada; Ishma Annisa; Yogi Rahmadani; Irma Masfia; Zulfa Fahmy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2025)
Support from the social environment has a significant impact on the development of children with special needs(Efendi, 2017). ADHD or Attention Deficit Hyperactivity Disorder is a neurobiological disorder that is common in children and can affect their ability to learn and interact socially. The way ADHD children interact is quite different from other people in general, because they have difficulty interacting with their environment, like to daydream, tend to move actively and cannot focus on listening or paying attention when other people are talking.This field research is qualitative in nature with a case study research design using interview and observation methods. Research subjects were chosen deliberately using purposive sampling.The origins of ADHD in a child often involve a variety of complex factors, and a lack of affection can be one of them. As time goes by, the subject is able to share with his friends and has quite good social relations. In addition, the ability to store their own things shows that they are making progress in aspects of daily life that reflect a growing level of independence. The results of this research are that social support, especially from peers and teachers in inclusive schools, plays a positive role in improving the socialization of children with ADHD.